A Semantic Distinction between Nafs and Qalb in the Qur'an - Muhammad Alif Rizieq Fathan; Kharis Nugroho (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze and compare the meanings of the terms nafs and qalb in the Qur'an. In many previous studies, these two terms are often treated as synonyms without sufficient linguistic and contextual analysis. This research seeks to clarify their semantic distinctions based on Qur'anic usage and classical exegetical explanations. Methodology: This study employs library research using the first variety of maudhu'i (thematic) interpretation. The analysis begins by tracing all Qur'anic verses containing the terms nafs and qalb along with their derivative forms. The basic meanings of each term are determined through Arabic-Arabic dictionaries, followed by contextual analysis based on classical Qur’anic commentaries that emphasize linguistic aspects. Results: The findings reveal that the term nafs is consistently used in the Qur’an to refer to human beings as complete entities, functioning as subjects of action and bearers of moral responsibility. In contrast, the term qalb refers to the inner center of human consciousness that functions to understand, believe, and respond to the truth. The study demonstrates that nafs and qalb are not used as absolute synonyms but occupy distinct semantic fields and functions within the Qur’anic discourse. Applications: This study reinforces the linguistic principle that differences in Qur’anic terminology indicate differences in meaning when supported by linguistic and contextual evidence. By applying the first variety of maudhu‘i interpretation, this research contributes to Qur’anic semantic studies and provides a methodological reference for distinguishing closely related Qur’anic terms based on textual usage rather than external conceptual assumptions.